Using the Consolidated Framework for Implementation Research to implement and evaluate national surgical planning. Issue 2 (13th July 2017) - Saluja, Saurabh; Silverstein, Allison; Mukhopadhyay, Swagoto; Lin, Yihan; Raykar, Nakul; Keshavjee, Salmaan; Samad, Lubna; Meara, John G
Abstract : The Lancet Commission on Global Surgery defined six surgical indicators and a framework for a national surgical plan that aimed to incorporate surgical care as a part of global public health. Multiple countries have since begun national surgical planning; each faces unique challenges in doing so. Implementation science can be used to more systematically explain this heterogeneous process, guide implementation efforts and ultimately evaluate progress. We describe our intervention using the Consolidated Framework for Implementation Research. This framework requires identifying characteristics of the intervention, the individuals involved, the inner and outer setting of the intervention, and finally describing implementation processes. By hosting a consultative symposium with clinicians and policy makers from around the world, we are able to specify key aspects of each element of this framework. We define our intervention as the incorporation of surgical care into public health planning, identify local champions as the key individuals involved, and describe elements of the inner and outer settings. Ultimately we describe top-down and bottom-up models that are distinct implementation processes. With the Consolidated Framework for Implementation Research, we are able to identify specific strategic models that can be used by implementers in various settings. While the integration of surgical care into public health throughout the world may seem like an insurmountable challenge, this work adds to a growing effort that seeks to find a way forward.